Developing resilience to England's future droughts: Time for cap and trade?. (1st February 2015) - Mitchell, Gordon; McDonald, Adrian
Abstract: Much of England is seriously water stressed and future droughts will present major challenges to the water industry if socially and economically damaging supply restrictions are to be avoided. Demand management is seen as a key mechanism for alleviating water stress, yet there are no truly effective incentives to encourage widespread adoption of the behavioural and technological demand management practices available. Water pricing could promote conservation, but on its own it is an inefficient tool for dealing with short term restriction in water supply. Raising prices over the short term in response to a drought is likely to be ineffectual in lowering demand sufficiently; conversely, maintaining high prices over the long term implies costs to the consumer which are needlessly high most of the time. We propose a system for developing resilience to drought in highly water stressed areas, based on a cap and trade (C&T) model. The system would represent a significant innovation in England's water market. However, international experience shows that C&T is successful in other sectors, and need not be overly complex. Here, we open the debate on how a C&T system might work in England. Highlights: A water cap and trade system is proposed to develop resilience against future drought in England. The proposal is exploratory, and seeks to generate debate in the UK water sector. Operational principles of the proposed scheme are described and discussed. Vignettes for different consumer groups illustrate the scheme in action. Some likely questions about scheme operation are identified and discussed.